Sublanguage in Machine Translation - Seljan, Sanja (2000)
Restriction of the source text in the narrow domain of science, technology, weather bulletins, stock market reports, manuals etc. is one way to diminish ambiguity problems of translation. Adequate analysis of the input text is a key to successful ma-chine translation (MT). Limited, but consistent grammar, vocabulary, syntax and semantics promise high-quality automatic translation, which can pay off only in long terms. The sublanguage reflects the knowledge which is on the higher level than common knowledge. Combination of lin-guistic theory and statistical methods seem to give best re-sults. The quality of machine translated texts can go up to 95% and is sufficient for information transfer, although it can be improved by post-editing.
Projekt MZOS
ENG